Iso-conversional kinetic and thermodynamic analysis of catalytic pyrolysis for palm oil wastes - Hii, Siaw Weii; Chin, Lai Fui; Fanthagiro Rossi Stuard, Majing; Lim, Huei Yeong; Chung Loong, Yiin; Loy, Adrian Chun Minh; Suzana, Yusup; Quitain, Armando T.; Acda, Menandro N.; Elisabeth, Rianawati (Elsevier, 2022)
This chapter presents the comparative studies related to the kinetic and thermodynamic analysis of the pyrolysis of oil palm frond (OPF) and oil palm trunk (OPT) that are investigated in the absence and presence of OPF ash, OPT ash, and OPF/OPT ash using thermogravimetric approach (TGA). OPF ash, OPT ash, and OPF/OPT ash are used as natural catalysts in the pyrolysis process of palm oil wastes. The experiments are conducted at various heating rates ranging 10–100 K min−1 from temperature of 323K to 1,173K. Iso-conversional kinetic models such as Coats-Redfern, Vyazovkin, and Miura-Maki model are the selected kinetic models to predict the kinetic parameters such as activation energy (EA) and preexponential factor. The average EA values ranged 28.49–211.69 kJ.mol−1 and 44.00–168.06 kJ.mol−1 for pyrolysis of OPF and OPT, respectively. Meanwhile, the average EA values ranged from 22.66–182.91 kJ.mol−1 and 36.86–269.67 kJ.mol−1 for the catalytic pyrolysis of OPF and OPT respectively.